Comparative analysis of serum lipid profiles in ischemic and hemorrhagic stroke: A retrospective cross-sectional study - Amran, Muhammad Yunus; Punala Putra N, Muhammad Mario; Muhlizah Nurhikmah S., Andini Rezky; Helariani Panti, Dwi Santa; Gunadi, Siti Giranti Ardilia (Acta Biomedica Atenei Parmensis, 2025)
Background and Aim: Stroke continues to present a global burden of disability, commonly presenting with symptoms such as headache, nausea, vomiting, and altered motor function. Stroke is classified into two major types: Hemorrhagic Stroke (HS), when the brain is bleeding; and Ischemic Stroke (IS), when a blockage prevents blood from flowing in the brain. Lipid level is an established risk factor for stroke, so patients with poor lipid regulation have a higher risk of suffering stroke. This study aimed to compare the serum lipid profiles of patients diagnosed with IS and HS. Methods: This study was an analytical (observational) study with a retrospective cross-sectional design. Demographic data and lipid profiles were obtained from patient medical records to compare lipid profiles and lipid ratios of the two stroke types. Results: Comparison of lipid profiles between the two groups revealed no significant difference in terms of total cholesterol (TC) (p=0.317), high-density lipoprotein (HDL) (p=0.94), low-density lipoprotein (LDL) (p=0.516), and triglyceride (TG) (p=0.356). Similarly, comparisons of lipid ratios showed no statistically significant differences in TC/HDL (p=0.926), LDL/HDL (p=0.788), and TG/HDL (p=0.166) between IS and HS patients. Conclusions: Despite higher mean serum lipid values and lipid ratios (TC/HDL, LDL/HDL, TG/HDL) among IS patients in the clinical setting compared to HS patients, statistically significant differences were not detected. Further large-scale studies should be conducted to clarify the clinical significance of lipid profiles in different stroke subtypes.